Flipbook Berdiferensiasi Materi Aku dan Lingkungan Sekitarku Berlandaskan Tri Hita Karana untuk Siswa Sekolah Dasar - Gede Aditya Wiguna; I G Agung Jaya Suryawan; I Ketut Ngurah Ardiawan (cendekia citra gemilang, 2026)
Conventional, monotonous, and uniform learning approaches in elementary schools often fail to accommodate diverse student learning styles and lead to a decline in ecological awareness regarding environmental topics. This study aims to develop an innovative media in the form of a differentiated digital flipbook on the topic